Sovereign Default, Private Sector Creditors and the IFIs - Boz, Emine (IMF Working Papers; Working Paper ;, 2009)
This paper builds a model of a sovereign borrower that has access to credit from private sector creditors and an IFI. Private sector creditors and the IFI offer different debt contracts that are modelled based on the institutional frameworks of these two types of debt. We analyze the decisions of a sovereign on how to allocate its borrowing needs between these two types of creditors, and when to default on its debt to the private sector creditor. The numerical analysis shows that, consistent with the data; the model predicts countercyclical IFI debt along with procyclical commercial debt flows, also matching other features of the data such as frequency of IFI borrowing and mean IFI debt stock.